Playing the Hypercube – Using Augmented Reality to Enhance a Multimodal Musical Performance - Souza, Alyson Matheus de Carvalho; Manzolli, Jônatas; Campos, Cléber Da Silveira; Rennó-Costa, César (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais do XXIV Simpósio de Realidade Virtual e Aumentada, 2022)
Multimodal performances aggregate multiple forms of interaction and stimulation to create artistical masterpieces. One of those performances is the Ode to Christus Hypercubus, by Jônatas Manzolli. To enhance the original version of this performance and add new layers of stimulation and interaction, an Augmented Reality (AR) experience was developed. This paper describes the development of this application, all the artistic concepts that were part of the development, and the technologies used to create the final experience. Finally, the paper describes a live performance using this AR interface in a real setting during an exhibition of the Ode to Christus Hypercubus.